Compositional analysis of Intermountain Ware pottery manufacturing areas in western Wyoming, USA. (April 2018) - Finley, Judson Byrd; Scheiber, Laura L.; Ferguson, Jeffrey R.
Abstract: In this study we examine 50 sherds from four archaeological sites to understand ceramic vessel source area variation in western Wyoming. Intermountain Ware ceramics are a diagnostic marker of Shoshone ethnicity, and our central hypothesis explores changing mobility during the Late Prehistoric and Historic Periods, ca. 1500–1870 CE. We use neutron activation analysis (NAA) for bulk paste chemical analysis and thin-section petrography to characterize clay and temper mineralogy. NAA places ceramic artifacts into eight groups with little overlap between sites in southwest and northwest Wyoming. Temper composition supports NAA groups indicating that ceramic vessels in this sample were made locally and not transported long distances before their eventual discard. Highlights: NAA of 50 Intermountain Ware pottery sherds from four western Wyoming archaeological site forms 8 compositional groups Petrographic analysis of temper from 35 of 50 sherds forms 10 distinct temper groups Local production and discard of pottery vessels among hunter-gatherers living in the mountains of western Wyoming